In situ immunopathological changes in cutaneous leishmaniasis due to Leishmania donovani. (March 2017) - Manamperi, N. H.; Oghumu, S.; Pathirana, N.; de Silva, M. V. C.; Abeyewickreme, W.; Satoskar, A. R.; Karunaweera, N. D.
Summary: Cutaneous leishmaniasis in Sri Lanka is a newly established parasitic disease caused by the usually visceralizing Leishmania donovani . Skin lesions manifest as non‐itchy, non‐tender papules, nodules or ulcers. In situ cytokine expression provides clues for immunopathogenesis of this localized form of disease. Skin biopsies from 58 patients were analyzed for histological appearance and in situ cytokine expression of T‐helper 1 (Th1) and T‐helper 2 (Th2) cytokines, namely interferon (IFN)‐γ, interleukin (IL)‐12A, tumor necrosis factor (TNF)‐α, IL‐4 and IL‐10 by real‐time RT‐PCR. Significant up‐regulation of the Th1 cytokine IFN‐γ and down‐regulation of the Th2 cytokine IL‐4 were seen in patients compared to healthy controls. Significantly elevated tissue expression of IFN‐γ and TNF‐α was seen in lesions that presented later than 6 months from the time of onset, while IL‐4 expression was more prominent in lesions that responded poorly to antimony therapy. A prominent Th1 response appears to support resolving of lesions, whereas a Th2‐biased milieu tends to favor poor responsiveness to antimony and delayed lesion healing in L. donovani infections in Sri Lanka.